Ivy Aberdeen's letter to the world - Blake, Ashley Herring (Little, Brown and Co., 2018)
"Twelve-year-old Ivy Aberdeen's house is destroyed in a tornado, and in the aftermath of the storm, she begins to develop feelings for another girl at school"--Provided by publisher.